2021
DOI: 10.1155/2021/5579369
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Inulin Modulates the Gut Microbiota and Improves Insulin Sensitivity in Prediabetes

Abstract: Aims. Accumulating evidence indicates gut microbiota dysbiosis is involved in metabolic disorders, including prediabetes. The prebiotic inulin has been frequently reported to exert beneficial effects on the host metabolism. Here, we aimed to evaluate whether dietary supplementation with inulin modulates gut microbiota structure in prediabetes, affecting glucose and lipid metabolism. Methods. We performed a prospective single-arm study. A total of 49 subjects with prediabetes (WHO 1999 criteria) were voluntaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Therefore, gut microbiota may also participate in the pathogenesis of several metabolic disorders, such as obesity, diabetes mellitus, and GDM ( Cani et al, 2014 ; Zhang et al, 2015 ; Rowland et al, 2018 ; Cortez et al, 2019 ). Prebiotics can exert positive effects on the maintenance of host metabolic homeostasis, which are mainly mediated by the gut microbiota ( Khanum et al, 2000 ; Wang et al, 2021 ). ITF, one of the crucial prebiotics, have been demonstrated to be effective in the treatment of T2DM ( Dehghan et al, 2014a ; Zhang et al, 2018 ), while data on the effects of symbiotic supplementation on markers of insulin metabolism and lipid concentrations in GDM are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, gut microbiota may also participate in the pathogenesis of several metabolic disorders, such as obesity, diabetes mellitus, and GDM ( Cani et al, 2014 ; Zhang et al, 2015 ; Rowland et al, 2018 ; Cortez et al, 2019 ). Prebiotics can exert positive effects on the maintenance of host metabolic homeostasis, which are mainly mediated by the gut microbiota ( Khanum et al, 2000 ; Wang et al, 2021 ). ITF, one of the crucial prebiotics, have been demonstrated to be effective in the treatment of T2DM ( Dehghan et al, 2014a ; Zhang et al, 2018 ), while data on the effects of symbiotic supplementation on markers of insulin metabolism and lipid concentrations in GDM are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have revealed the effect of inulin supplementation on glucose and lipid metabolism in genetically obese mice [ 11 ], or wild-type mice [ 12 , 13 ] or rats [ 14 ] after induction of dietary obesity. Human studies [ 15 , 16 ] have also shown that inulin intake improves glycolipid metabolism, as it is fermented into SCFAs by gut microbiota in the situation of energy excess due to the high-fat and high-sucrose diet (HFHSD), or in the presence of glucose intolerance or obesity.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with previous studies that found supplementation with inulin and/or FOS does not have significant independent effects on fasting glycemia and insulinemia, HOMA-IR index or lipid profile ( 31–35 ). Nonetheless, others demonstrated that ITF-prebiotics may have lipid-lowering ( 36 ) or glucose-lowering ( 13 , 37 , 38 ) effects, particularly among those with impaired fasting glycemia or hypercholesterolemia. In the present study we recruited individuals with obesity who were otherwise healthy (i.e., without hypertension, glucose abnormalities, and dyslipidemia), and found trends for attenuated reduction in glucose and LDL-C and augmented reduction in HDL-C in the ITF-subgroup relative to control, despite similar weight loss.…”
Section: Discussionmentioning
confidence: 99%